Nutritional Status and Related Factors of Children Attending Pediatric Outpatient Department at A Tertiary Care Hospital in Sindh, Pakistan - Dr. Laila Pirzado, Dr. Sadaruddin Arijo, Dr. Neelum Dileep, Dr. Suman Rashdi, Dr. Mehwish Asghar, Prof. Dr. Ali Akbar Siyal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Malnutrition is a serious, common and potentially life-threatening complication being the most important cause in contributing to mortality and morbidity of children under five years of age. Although the term malnutrition is considered to include both undernutrition and over-nutrition, but the greater risk for mortality and morbidity rates are in undernourished patients. Objective: To determine frequency of underweight, overwight, and related factors among children under 5 years of age. Duration and Place of the study: This cross-sectional research was conducted at Pediatric OPD, Peoples University of Medical and Health Sciences for Women (PUMHSFW) Hospital, Nawab Shah between 5.10.2019 to 04-04-2020 Material and Methods: The study enrolled 377 children under five years of age. Data were collected through interviews with mothers/caregivers, anthropometric measurements, and WHO growth charts for Z-scores of weight-for-age (W/A), weight-for-height (W/H), and height-for-age (H/A). Result: Out of 377 study subjects, 42.44% mothers were educated, 53% breasted exclusively and 47.57% children were immunized. Out of 377 children 92.31% were underweight, 95.76% stunted and 85.41% wasted. 81.96% had all three conditions of underweight, stunted and wasted. Among underweight, 43.10%, stunted 44.32% and wasting 32.61% mothers were educated. Age of the mother in underweight was 14.37% less than 20 years of age, 63.22% between 20 to 35 years and 22.41% were 35 years and above. In stunted, 14.96% were less than 20 years of age, 62.05% between 20 to 35 years and 22.99% were 35 years and above. Among wasted, 13.98% were less than 20 years of age, 62.11% between 20 to 35 years and 23.91% were 35 years and above. Conclusion: The study findings reveal the high prevalence of underweight 92.31%, Stunting 95.76% and wasting 85.41% (322) which are almost double of the national as well as Sindh figures documented in community-based surveys like NNS 2018, PDHS 2018 and MICS 2019. Keywords: Malnutrition, Underweight, Stunting, Wasting, Overweight, Breastfeeding, Pakistan.